Systemic antibiotics for chronic suppurative otitis media - Chong, LY; Head, K; Webster, KE; Daw, J; Richmond, P; Snelling, T; Bhutta, MF; Schilder, AGM; Burton, MJ; Brennan-Jones, CG (Cochrane Collaboration, 2021)
Background Chronic suppurative otitis media (CSOM) is a chronic inflammation and infection of the middle ear and mastoid cavity, characterised by ear discharge (otorrhoea) through a perforated tympanic membrane. The predominant symptoms of CSOM are ear discharge and hearing loss.